SOCIO-CULTURAL ENVIRONMENT OF THE UNIVERSITY AS A CONDITION OF STUDENT DEVELOPMENT AND A SUBJECT OF MANAGEMENT - Tatyana A. Shulgina (Высшее образование в России)
The article views the approaches to socio-cultural environment formation at higher education institution and considers its effectiveness criteria. It determines the monitoring position in management of processes of socio-cultural environment formation of taking into accont the context of competency approach in education.